Review of high-value agriculture in the Philippines with comprehensive subsectoral focus: Livestock industries - Sonny N. Domingo; Ma. Divina C. Olaguera (Philippine Institute for Development Studies (PIDS), 2017)
Enhancing the performance of the Philippine agriculture sector remains a key input to economic growth and inclusivity. Focus of development interventions in recent years have been on crops, particularly on the major grain staples. Shifting attention to more competitive and higher value commodities like livestock would do much in enhancing the livelihoods of smallholder farmers, as well as micro, small, and medium-sized enterprises within the sector. While the subsector presents a glimmer of light in local agriculture, its industries are beset with production and marketing issues. The main objective of this paper is to review the status and performance of the Philippine livestock sector. This review provides discourse on the livestock subsector's performance over the years and looks into ways of bettering outputs and competitive advantages both within domestic commodity systems and beyond.
Keywords: 330; Philippines Livestock Sector; Industry Analysis